2007
DOI: 10.1243/09576509jpe315
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into wave—current interactions in marine current turbines

Abstract: The paper looks at the use of blade element-momentum theory for predicting the torque and thrust on a marine current turbine and the results of wave tank tests using a 400 mm-diameter rotor model. To include the effects of waves, linear wave theory particle velocities and accelerations were integrated into the mathematical model. Comparison with test data shows a good agreement which implies that the theory can be effective in analysing the wave-current interactions in marine current turbines. The paper also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 3 publications
2
28
0
Order By: Relevance
“…The Reynolds number at 75% radius was between 0.87-1.52 × 10 5 in the present cases. Although it was still lower than that expected of the prototype tidal turbines, it was at the same level compared to the previous towing model tests [3,4,6,12]. The carriage velocity of 0.56 m s −1 and 0.68 m s −1 is equivalent to 2.8 m s −1 and 3.4 m s −1 in full scale respectively, which are the general rated current speed for tidal turbines.…”
Section: Results and Discussion Average Power And Trust Coefficientsmentioning
confidence: 54%
See 1 more Smart Citation
“…The Reynolds number at 75% radius was between 0.87-1.52 × 10 5 in the present cases. Although it was still lower than that expected of the prototype tidal turbines, it was at the same level compared to the previous towing model tests [3,4,6,12]. The carriage velocity of 0.56 m s −1 and 0.68 m s −1 is equivalent to 2.8 m s −1 and 3.4 m s −1 in full scale respectively, which are the general rated current speed for tidal turbines.…”
Section: Results and Discussion Average Power And Trust Coefficientsmentioning
confidence: 54%
“…Barltrop et al [4] performed experiments using a 400 mm diameter rotor in a towing tank with the presence of regular waves. The average thrust and torque were found to be independent with the wave frequencies or wave heights.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Barltrop and co-workers studied the effects of waves towards loading on turbine blades using an extended BEM model. It was found that a shorter wave might lead to the stalling of the blade and consequently, increase the axial loading on it [84] Experiments were conducted to validate the model. Their process of aerofoil selection is different from that of Bahaj's team.…”
Section: Design Considerationmentioning
confidence: 99%
“…Several groups have investigated the influence of surface waves on tidal turbine performance [4][5][6][7]. These researchers conducted experiments to measure the turbine performance with and without the presence of surface waves.…”
Section: Introductionmentioning
confidence: 99%